2016
DOI: 10.1007/s00068-016-0659-4
|View full text |Cite
|
Sign up to set email alerts
|

Low failure rate by means of DLBP fixation of undisplaced femoral neck fractures

Abstract: BackgroundThis study evaluated the clinical results of a new implant in the internal fixation of undisplaced femoral neck fractures.MethodIrrespective of their age, 149 patients with undisplaced (Garden I and II) femoral neck fractures were included in a prospective multicentre clinical cohort study and were treated by internal fixation by means of the Dynamic Locking Blade Plate (DLBP). The mean age was 69 years and the follow-up at least one year.ResultsThe DLBP fixation resulted in 6 out of 149 failures cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…In a prospective multicenter cohort study in the Netherlands 172 patients with an undisplaced FNF were treated with the DLBP. The results of this study showed a failure rate of 4% [13]. Another recent prospective cohort study of 106 patients of 60 years and younger with displaced FNF demonstrated a DLBP related failure rate of 13.2% [14].…”
Section: Introductionsupporting
confidence: 43%
See 2 more Smart Citations
“…In a prospective multicenter cohort study in the Netherlands 172 patients with an undisplaced FNF were treated with the DLBP. The results of this study showed a failure rate of 4% [13]. Another recent prospective cohort study of 106 patients of 60 years and younger with displaced FNF demonstrated a DLBP related failure rate of 13.2% [14].…”
Section: Introductionsupporting
confidence: 43%
“…The DLBP is a new implant that is on the market since 2010. Today's evidence for this implant is not as widespread as for the DHS, but the results from (non randomized) earlier studies are promising [13,14]. The outcome of the DEFENDD trial will provide high-level evidence of which implant is favorable for the treatment of femoral neck fractures in young patients (≤65 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent paper describing the outcome of 320 patients treated with internal fixation reported an AVN rate of 4.5% for undisplaced and 11.1% for displaced intracapsular fractures with a minimum follow-up of two years [12]. This doubling of incidence further supports that osteosynthetic treatment should only be used in undisplaced femoral neck fractures [10,19,20].…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have found that the stability of femoral neck fractures is of great signi cance to the revascularization of the femoral head, and plays an important role in promoting bone healing and reducing the rate of femoral head necrosis [14,15]. Moreover, It is reported that a large volume of implants may interfere with the revascularization of the femoral head and increase the incidence of femoral head necrosis [16]. The diameter of the screw bolt and the anti-rotation screw of FNS was 10 mm and 6.4 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%